MOLECULAR PATHOGENESIS OF CLOSTRIDIUM DIFFICILE AND ITS ROLE IN ANTIBIOTIC-ASSOCIATED DIARRHEA - Mrs. Madhuri Musunuru; Mrs. T. Uma Maheswari (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Clostridium difficile (C. difficile) is a leading cause of antibiotic-associated diarrhea (AAD), with increasing prevalence due to its toxin-mediated pathogenesis, microbiota disruption, and antibiotic resistance. This study investigates the molecular mechanisms of C. difficile infection (CDI), focusing on toxin production, microbiota dysbiosis, antimicrobial resistance, and immune responses to identify potential therapeutic interventions. Methods: Five C. difficile clinical isolates (CDI-001 to CDI-005) were analyzed for toxin production using Enzyme-Linked Immunosorbent Assay (ELISA), microbiota composition via 16S rRNA sequencing, and antibiotic resistance through Minimum Inhibitory Concentrations (MIC) testing. Host immune responses were assessed using multiplex cytokine assays, and genomic sequencing identified resistance-associated mutations. Results: TcdA and TcdB levels varied across strains, with CDI-003 exhibiting the highest TcdA (50.1 ng/mL) and CDI-002 the highest TcdB (60.2 ng/mL). CDI patients exhibited reduced microbial diversity (Shannon index-1.9 vs. 3.8 in controls, Simpson index-0.45 vs. 0.85). Ciprofloxacin and clindamycin resistance was 55% and 40%, respectively, while fidaxomicin retained 97% susceptibility. Cytokine analysis revealed significantly elevated IL-6 (18.6 pg/mL) and IL-8 (24.2 pg/mL) levels in CDI patients, suggesting immune dysregulation. Conclusion: C. difficile infection is driven by toxin overproduction, gut microbiota disruption, and antibiotic resistance. Targeted therapies restoring microbiota balance and neutralizing toxins are essential for reducing recurrence and severity. Future research should explore microbiome-based and immunomodulatory treatments to improve CDI management.